ANALISIS FAKTOR PERMASALAHAN PELAYANAN PENYEDIAAN AIR BERSIH OLEH PERUMDA AIR MINUM BANYUMILI KABUPATEN REMBANG - Wibisono, Khadis Satria; Manar, Dzunuwanus Ghulam; Marlina, Neny - (Journal of Politic and Government Studies, 2024)
Perumda Air Minum Banyumili is a regionally owned business entity in Rembang Regency that provides public services in terms of clean water provision regulated by Rembang Regency Regional Regulation No.16 of 2019 concerning Perumda Air Minum Banyumili Rembang Regency. This study aims to analyze and identify the factors of service problems as well as the efforts of Perumda Air Minum Banyumili to overcome service problems. The theory used is the Good Governance Theory from UNDP (United Nations Development Programme) using five indicators including accountability, transparency, responsiveness, rule of law, and effectiveness and efficiency. The method used is qualitative descriptive, data collection is carried out through interviews and documentation studies. The results of the study show that the main factor of the problem of clean water services is the source of raw water. Of the five indicators, four of them are transparency, responsiveness, legal rules, and effectiveness and efficiency show service problems. Meanwhile, accountability shows good service responsibility including supervision, reporting, and evaluation. The efforts made by Perumda Air Minum Banyumili in overcoming problems have not been able to solve the existing service problems. This research will provide information and understanding related to the factors of clean water service problems and the efforts made by Perumda Air Minum Banyumili as a service provider. It is hoped that this research can be a recommendation and evaluation in efforts to improve and improve clean water supply services in Rembang Regency with the implementation of good governance